Arts and aesthetics in a globalizing world - Kaur, Raminder; Dave Mukherji, Parul editor (London, UK Bloomsbury Academic, an imprint of Bloomsbury Publishing Plc, 2014)
"Art and Aesthetics in a Globalizing World investigates art and aesthetics in their widest senses and experiences, from a variety of perspectives branching from the metaphysical to the political. Moving beyond art as an expression of the inner mind and invention of the individual self, the volume bridges the gap between changing perceptions of contemporary art and aesthetics, and maps globalising currents in a number of contexts and regions. The volume includes an impressive variety of case studies offered by established leaders in the field and original and emergent scholarly talent covering areas in India, Nepal, Indonesia, Iran, Russia, Rwanda and Germany as well as providing transnational or diasporic perspectives. From the contradictory demands made on successful artists from the south in the global art world such as Anish Kapoor, to images of war and puppetry created by female political prisoners, the volume compels creative and political interpretations of the ever-changing and globalizing terrain of arts and aesthetics. Art and Aesthetics in a Globalizing World will be important reading for students and scholars of the anthropology of art, art, and art history, and media, film and cultural studies"--Provided by publisher.
Introduction / Raminder Kaur (University of Sussex) and Parul Dave-Mukherji (Jawaharlal Nehru University) -- Of mockery and mimicking : Gaganendranath Tagore's critique of Henri Bergson's Laughter (1911) / Emilia Terracciano (Courtauld Institute of Art and University College London) -- The return of the Aura : Anish Kapoor, the studio and the world / Denis Vidal (IRD/Paris Diderot/EHESS) -- The practice of art : an alternative view of contemporary art-making in Tehran / Leili Sreberny-Mohammadi (New York University) -- Art under siege : perils and possibilities of aesthetic forms in a globalising world / Patricia Spyer (Leiden University) -- Hot bricolage : magical mimesis in modern India / Christopher Pinney (University College London) -- Rethinking waste : time, obsolescence, diversity and democracy / Shiv Visvanatham (O.P. Jindal Global University) -- Slaps, beatings, laughter, Adda, puppet shows : Naxal women prisoners in Calcutta and the art of happiness in captivity / Atreyee Sen (University of Manchester) -- Rwanda : healing and the aesthetics of poetry / Andrea Grieder (University of Zurich and EHESS Paris) -- The aesthetics of diaspora : sensual milieus and literary worlds / Pnina Werbner (Keele University) and Mattia Fumanti (University of St. Andrews) -- For love's sake? : changing landscapes of sonic and visual aesthetics of weddings in the Kathmandu Valley (Nepal) / Christiane Brosius (University of Heidelberg) -- The aesthetics of pirate modernities : Bhojpuri cinema and the underclasses / Akshaya Kumar (University of Glasgow) -- Intimacy out of place : on the workings of smell in an exhibition on human sexuality / Susanne Schmitt (University of Munich) -- Consuming culture : the refiguration of aesthetics in Nagaland cultural tourism in India's north east / Soumendra Mohan Patnaik (University of Delhi) -- Reflections upon the meaning of contemporary digital image-making practices in India / Giulia Battaglia (Musée du Quai Branly, Paris) and Paolo Favero (University of Antwerp) -- Reflections / Marilyn Strathern (University of Cambridge)
Includes bibliographical references and index.
Keywords: Arts and globalization; Arts, Modern -- 21st century; Aesthetics, Modern -- 21st century